Association and influence of risk criteria to decision making of green building investment in higher educational campuses - Al Qaifi, Gamal Nabil Ali (UNIVERSITI TEKNOLOGI MALAYSIA, 2016)
Sustainable development is significantly increasing worldwide by earning a place in the construction industry as an essential milestone for a better future. Universities’ role as innovation centres enforces their part in functioning sustainable measures to achieve sustainable goals such as green building investment inside Higher Educational Campuses. However, risks of uncertainties challenge universities key leaders’ decision making to invest in this development. This paper aims to determine the level of risk criteria’s influence to decision making of stakeholders for green building investment in higher educational campuses. A quantitative approach using Likert Scale was employed by developing and distributing matrix questionnaire sets to the Office of Assets and Development at Universiti Teknologi Malaysia, Johor, Malaysia. A descriptive and correlation analysis by SPSS version 16 were used to determine the level of risk criteria’s influence to decision making of green building investment as well as the association level of risk criteria. The risk sub-criteria have been divided into six themes (criteria), precisely (Government, Financial, Stakeholders, Compliance, Knowledge and Tools). It has been found that Risk criteria have scored a maximum mean score of 3 out of 5 which implies a moderate influence to decision making of green building investment in higher educational campuses. The association level between these criteria have been proven to be significant with a Pearson Correlation that varies from (87% - 97%) which presents a correlation of influence to decision making not only by one criteria particularly but all of them at the same time. The obstacles and uncertainties represented by risks have been found to be of a hindrance to the decision making process of green building investment in higher educational campuses from the respondents’ point of view. This study reflects the importance of mitigating and managing these risks at an earlier stage to avoid problematic issues of sustainable development projects inside universities campuses.